2007
DOI: 10.1007/s10439-007-9284-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of Composite Analogue Femur Constructs under High Activity Loading

Abstract: Synthetic mechanical analogue bone models are valuable tools for consistent analysis of implant performance in both equilibrium and fatigue biomechanical testing. Use of these models has previously been limited by the poor fatigue performance when tested under realistic service loads. An objective was to determine whether a new analogue bone model (Fourth-Generation) using enhanced analogue cortical bone provides significantly improved resistance to high load fracture and fatigue as compared to the current (Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 37 publications
0
42
0
1
Order By: Relevance
“…All cadaveric specimens comminuted far earlier than the proposed final time under axial load in the circulating fluid testing environment required by the ASTM standard. The synthetic scapulae we used provided a more homogenous test bed than cadaveric specimens, and they are more anatomically relevant than foam blocks as used in previous studies [8,23,33]. Although fatigue testing is not defined for this model, this substrate (fourthgeneration composite bones) has been shown to have similar biomechanical properties to human bone [20,41,42] and has been used by others for glenoid prosthesis testing [34].…”
Section: Discussionmentioning
confidence: 99%
“…All cadaveric specimens comminuted far earlier than the proposed final time under axial load in the circulating fluid testing environment required by the ASTM standard. The synthetic scapulae we used provided a more homogenous test bed than cadaveric specimens, and they are more anatomically relevant than foam blocks as used in previous studies [8,23,33]. Although fatigue testing is not defined for this model, this substrate (fourthgeneration composite bones) has been shown to have similar biomechanical properties to human bone [20,41,42] and has been used by others for glenoid prosthesis testing [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, artificial bones were used instead of cadaver bones. It is known that the fourth-generation Sawbones are very close to human bones regarding their mechanical properties [7,8]. However, they present a young and healthy population and not a very broad cross-section of the population in terms of mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The currently available composite bones are fourth-generation composite bones where a solid rigid PU-foam is used as cancellous core material while a mixture of glass fibres and epoxy resin was pressure injected around the foam to mimic cortical bone. Chong et al (Chong et al, 2007a, Chong et al, 2007b performed extensive mechanical testing with these synthetic bones and found out that the fourth-generation material has better fatigue behavior and modulus, strength and toughness behaviours a lot closer to literature values for fresh-frozen human bones than previous composite bones. Heiner (Heiner, 2008) tested stiffness of the composite femurs and tibias under bending, axial and torsional loading as well as measuring longitudinal strain distribution along the proximal-medial diaphysis of the femur.…”
Section: The Use Of Pu Foams In Orthopaedic Implant Testingmentioning
confidence: 72%